2010
DOI: 10.1007/s12649-010-9055-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CFB-Coal Fly Ash Clay Bricks and Their Characterisation

Abstract: The aim of this work was to test CFB-derived fly ash for its potential to get utilised in ceramic tilesmanufacturing by applying the sintering technique. The tested specimens were moulded using extrusion and fired at 1,050°C; a laboratory pilot-plant simulation of the industrial brick fabrication process was applied and the produced materials were afterwards tested for their microstructure and physical properties. Different types of clays were selected and characterised and various clay-ash mixtures were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…1). This indicated that class F ashes are more favorable to be used in the brick industry, which is already observed earlier [21].…”
Section: Global Sensitivity Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…1). This indicated that class F ashes are more favorable to be used in the brick industry, which is already observed earlier [21].…”
Section: Global Sensitivity Analysissupporting
confidence: 75%
“…The study considered the 302 cases available in the literature on the usage of fly [1,[3][4][5][7][8][9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29][30], bottom ashes [2,6,24,30], and pond ashes [5,13,14,31] in clay bricks.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Water absorption of diff erently shaped samples was evaluated in fired clay pieces by soaking in distilled water for 24 hours, according to standard procedure [12].…”
Section: Chemical and Technological Featuresmentioning
confidence: 99%
“…Fly ash can be considered as the world's fifth largest raw material resource [7]. Currently, one possible utilization of fly ash is in the synthesis of alkali-activated materials named geopolymers [8,9]. PC fly ash can successfully be used for the manufacturing of cement, building materials concrete, and concrete-admixed products [10], as it is categorized as a pozzolan, while CFB fly ash with a higher carbon content is broadly used as an insulator and adsorbent [6,11].…”
Section: Introductionmentioning
confidence: 99%